Comparison of the effects of high-load versus low-load resistance training on sport-specific performance parameters in youth cross-country skiers and biathletes: a pilot study - Wagner, C.-M.; Schmidt, T.; Warneke, K.; Keiner, M.; Schiemann, S. (2023)
In sports practice, cross-country ski athletes often incorporate maximum strength- or explosive strength training to their work-out routine. Hypertrophy training, especially in the upper body is generally recommended to be avoided, as increased bodyweight is thought to be detrimental for endurance performance. However, some authors indicated that peak oxygen uptake (VO2peak) is considerably influenced by the active muscle mass during exercise (Larsen et al., 2016). Therefore, it seems reasonable that upper-body hypertrophy could increase VO2peak in double poling (Wislof & Helgerud, 1998). However, various studies reported strong positive correlation between fat-free mass in the upper-body and DP performance (r= 0.69-0.92) (Osteras et al., 2016).